(untitled) (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2025)
The exploration of Parijoto (Medinilla speciosa Blume) continues to be increased because the color and content of anthocyanin compounds in Parijoto are interesting to study. Foodstuffs, especially fruits, which have a high level of consumption in society, need attention in their packaging and storage. The purpose of this study was to determine the profile of the food ingredient, in this case cherry tomatoes were used which had been coated with an edible ingredient added with Parijoto extract. The profile in question includes physical and organoleptic appearance, moisture content and mass of food ingredients. This study used UV-Vis and HPLC spectrophotometry to determine the anthocyanin content, both quantitatively and qualitatively. Testing the profile of each food ingredient using standard laboratory methods. The anthocyanin contents identified in Parijoto were Delfinidin-3-glycosides and Cyanidin-3-glycosides with a total content of 0.05065%w/w or 0.5065 mg/g. Foodstuffs packaged with edible coatings show a longer shelf life and minimal quality loss when compared to foodstuffs that are not coated. In addition, the coating made with the addition of Parijoto extract also showed a longer shelf life and minimal quality loss than tomatoes coated with an edible coating solution without Parijoto extract.